A complementary role for tetraspanin superfamily member CD151 and ADP purinergic P2Y12 receptor in platelets - Makkawi, Mohammed; Moheimani, Fatemeh; Alserihi, Raed; Howells, David; Wright, Mark; Ashman, Leonie; Jackson, Denise E. (Thrombosis and Haemostasis, 2015)
P2Y12 receptor is required for sustained activation of integrin αllbβ3, irreversible platelet aggregation and thrombus stabilisation. Tetraspanin superfamily member CD151 associates with integrin aNbp3 and plays critical roles in regulation of thrombus growth and stability in vivo. The possible functional relationship between P2Y12 and CD151 in a molecular cluster in platelets may affect thrombus formation. Hence our aim was to investigate the physical and functional requirements for this association in platelets. Our investigations reveal a specific and constitutive association between CD151 and P2Y12 receptor in human platelets shown by immunoprecipitation/western blot studies and by flow cytometry. Specifically, the prominent association involves CD151 with P2Y12 oligomers, and to a lesser extent P2Y12 monomers. This association is not altered by platelet aggregation induced by different agonists. There is also a distinct complex of tetraspanin CD151 with ADP purinergic receptor P2Y12 but not P2Y1. P2Y12 oligomer interaction with CD151 is selective as compared to other tetraspanins. To investigate the functional relationship between these receptors in platelets we used wild-type or CD151 knockout (KO) mice treated with either PBS or 50 mg/kg clopidogrel. CD151 KO mice treated with clopidogrel exhibited synergy in delayed kinetics of clot retraction, in PAR-4 and collagen-mediated platelet aggregation, platelet spreading on fibrinogen and without restricting cAMP inhibition. Clopidogrel treated CD151 KO arterioles showed smaller and less stable thrombi with increased tendency to embolise ex vivo and in vivo. These studies demonstrate a complementary role between CD151 and P2Y12 receptor in platelets in regulating thrombus growth and stability.
Keywords: Platelets; CD151; mice; clopidogrel; purinergic P2Y12